2016
DOI: 10.1128/mcb.01114-15
|View full text |Cite
|
Sign up to set email alerts
|

Novel MicroRNA Regulators of Atrial Natriuretic Peptide Production

Abstract: Atrial natriuretic peptide (ANP) has a central role in regulating blood pressure in humans. Recently, microRNA 425 (miR-425) was found to regulate ANP production by binding to the mRNA of NPPA, the gene encoding ANP. mRNAs typically contain multiple predicted microRNA (miRNA)-binding sites, and binding of different miRNAs may independently or coordinately regulate the expression of any given mRNA. We used a multifaceted screening strategy that integrates bioinformatics, next-generation sequencing data, human g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 37 publications
(52 reference statements)
0
18
0
1
Order By: Relevance
“…Although it was not detected in the present study, several researches in vivo and in vitro have demonstrated that excessive fluid volume would cause cardiomyocyte injury and apoptosis, which could induce a series of cardiovascular dysfunctions by impairing biochemical signal transduction, vascular tone adaptation, and baroreflex control of circulation . When HD patients are fluid overloaded, the sustained preload‐induced cardiomyocyte injury might lead to abnormal expression and production of bioactive substances that could disrupt BP regulation . However, the exact mechanism involved was not yet adequately established.…”
Section: Discussionmentioning
confidence: 66%
“…Although it was not detected in the present study, several researches in vivo and in vitro have demonstrated that excessive fluid volume would cause cardiomyocyte injury and apoptosis, which could induce a series of cardiovascular dysfunctions by impairing biochemical signal transduction, vascular tone adaptation, and baroreflex control of circulation . When HD patients are fluid overloaded, the sustained preload‐induced cardiomyocyte injury might lead to abnormal expression and production of bioactive substances that could disrupt BP regulation . However, the exact mechanism involved was not yet adequately established.…”
Section: Discussionmentioning
confidence: 66%
“…COS7 cells (obtained directly from American Type Culture Collection, CRL-1651) were cultured in Dulbecco’s modified Eagle’s medium supplemented with 10% fetal bovine serum, 2 mM L-glutamine, 200 U/ml penicillin, and 200 μg/ml streptomycin. Cardiomyocytes (CM) were differentiated from human embryonic stem cells (hESC, WA07, NIH Human Embryonic Stem Cell Registry Number 0067, generated by WiCell Research Institute) as previously described [ 10 ]. Human ESC-CMs have been well characterized and display functional and structural properties of primary human cardiomyocytes [ 11 , 12 ], including specifically their expression of NPPA , a hallmark of cardiomyocyte-specific expression.…”
Section: Methodsmentioning
confidence: 99%
“…Deep sequencing analysis identified rs61764044, a second variant located 123 nucleotides downstream of, and perfectly correlated with, rs5068 (r 2 = 1); the minor alleles of both variants are always co-inherited. Because of this perfect linkage disequilibrium, rs61764044 is also associated with increased plasma ANP levels, lower blood pressure, and reduced risk of hypertension [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, the ideas concerning local humoral mechanisms of BP regulation are being successfully developed, and the progress in this direction is quite significant (Burnier and Forni 2012, Mangiafico et al 2013, Markov 2005, Ruilope et al 2010. The role of kidneys and heart in BP maintenance is known and well-researched (Carlström et al 2015, Esler 2015, Qu et al 2016, Roman et al 2016, Wu et al 2016. The significance of the tonus of sections of autonomic nervous system in BP formation is discussed in (Bakris and Nathan 2014, Bhatt et al 2014, Mu et al 2011.…”
Section: Introductionmentioning
confidence: 99%